THE IMAGE OF WAR-TRAUMATIZED CHILDREN AND THE THEME OF CHILDHOOD IN THE WORKS OF O‘TKIR HOSHIMOV AND TOHIR MALIK: (In Comparison with English Literature) (SCIENCE TIME JOURNAL, 2025)
This article explores the depiction of children and the psychological, moral, and social aspects of childhood during wartime in the works of Uzbek writers O‘tkir Hoshimov and Tohir Malik. It analyzes the artistic portrayal of children who suffered from the consequences of war and provides a comparative study with similar representations in English literature—particularly in the works of Ian McEwan, William Golding, Michelle Magorian, and John Boyne. The paper highlights how war affects the human psyche, especially the world of childhood, and shows how the image of the child serves as a powerful medium for expressing human tragedy and ethical concerns.